2018
DOI: 10.1159/000487435
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report on 3-Weekly Paclitaxel Carboplatin Efficacy in Locally Advanced or Metastatic Squamous Vulvar Cancer

Abstract: In this brief report, we present our experience with 3-weekly paclitaxel-carboplatin chemotherapy for patients with vulvar cancer. Two patients with locally advanced disease had an impressive response allowing standard vulvar cancer surgery. One patient with metastatic disease had local stable disease though it was progressive in the lymph nodes. The available literature is sparse and retrospective. Based on promising results, however, a prospective multicenter study is mandatory in order to obtain full data i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
(17 reference statements)
0
11
0
Order By: Relevance
“… 81 An alternative strategy is the use of neoadjuvant chemotherapy with cisplatin or carboplatin and paclitaxel, to shrink the nodes prior to radiotherapy. 82 …”
Section: Surgical Management Of Vulvar Squamous Cell Carcinomamentioning
confidence: 99%
“… 81 An alternative strategy is the use of neoadjuvant chemotherapy with cisplatin or carboplatin and paclitaxel, to shrink the nodes prior to radiotherapy. 82 …”
Section: Surgical Management Of Vulvar Squamous Cell Carcinomamentioning
confidence: 99%
“…The combination of carboplatin and paclitaxel, as used in other gynaecological malignancies, has been evaluated with or without ifosfamide. Amant et al demonstrated that patients with locally advanced vulvar cancers treated with 3-weekly carboplatin and paclitaxel, responded sufficiently to be able to undergo surgery [ 35 ].…”
Section: Treatment Optionsmentioning
confidence: 99%
“…We must consider that the reported studies have not adequately assessed the combination of PTX + platinum with or without bevacizumab, which constitute the most used agents in gynecologic malignancies. This protocol was assessed in a small case series of 3 patients published by Amant et al, showing promising results [56]. The potential role of the immune checkpoint inhibitors has been recently evaluated by analyzing the expression of PD-L1, PD-1 and CD8 by immuno-histochemistry [57].…”
Section: Neoadjuvant Chemotherapymentioning
confidence: 99%